Cultural competence of nurses in Pudong New Area, Shanghai: a mixed-method study - Ma Li-Li; Jiang Hui; Peng You-Qing (Sciendo, 2020)
Cultural competence has gradually attracted attention from many countries, including China. This study was undertaken to determine the cultural competence of registered nurses in Shanghai, China, and to identify the cultural competence among registered nurses in Pudong New Area, Shanghai.